Analysis of PAI and Budi Pekerti Teaching Materials on National Character in the Merdeka Curriculum - Kusumawati Dewi, Wulan; Hermawan, Wawan; Taufiq Abdillah, Hilman (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This study aims to analyze the teaching materials for Islamic Religious Education (PAI) and Budi Pekerti in the Merdeka Curriculum related to the development of national character. The method used is a descriptive qualitative approach with content analysis techniques on Islamic Religious Education and Budi Pekerti textbooks from primary to secondary education levels. Data were collected through documentation techniques which included identifying, recording, and classifying relevant information. Data analysis was conducted by following six phases of content analysis which include unitizing, sampling, recording, reducing, inferring, and narrating. The main findings of the study show that each phase in the Merdeka Curriculum progressively teaches national character values, such as respect for human dignity, love for the country, democracy, social solidarity, and a just and prosperous society. The PAI and Budi Pekerti teaching materials successfully integrate these values in the context of character education, which is expected to form a generation that is noble, responsible, and sensitive to differences. This research makes an important contribution to the development of more effective teaching materials to instill the spirit of nationalism among students.